İlhanlı Hükümdarı Ebu Sa'id Han'a Ait Dört Yarlıg - (:unkn) unknown (My University, 2005)
0

As there are few decrees from medieval Iran which have survived to the present day, it is necessary to collect and publish them in their entirety. This article is a contibution to this project. It published, translates, and gives a commentary on the four Persian decrees (yarlig) written in Adharbaijan (Sultaniyya, Ribata al-Divan, Ardabil and Dar al-Mulk Tabriz) between the years 730-731/1330-1331. These decrees of Abu Sa‘id Khan (1317-1335) can be found in a volume (majmu‘a) of collected texts in the Kitabkhana-yi Milli-yi Malik Library (no. 3697) in Tehran. The decrees generally deal with taxes, tax collection difficulties and problems faced by the populace. The analysis of the decrees (yarlig) from a diplomatic and historical perpective both enriches the knowledge of the social, economic, and the administrative structure of the Ilhanid state and confirms the existing knowledge of chronicles of that period.
Four Decrees (Yarlıg) of the Ilkhanid Ruler Abu Sa'id Khan
Keywords: Tarih